DETEKSI BAKTERI Klebsiella pneumoniaePADA SPUTUM DENGAN METODE IMUNOSITOKIMIA MENGGUNAKAN ANTI OUTER MEMBRANE PROTEIN BERAT MOLEKUL 40 KDA Klebsiella pneumoniaeSEBAGAI ANTIBODI - Susilo, Joko; Sartono, Teguh R.; Sumarno, Sumarno (Jurnal Kedokteran Brawijaya, 2004)
Klebsiella pneumoniae (K. pneumoniae) is a normal flora in human Gastro Intestinal Tract. This strain of K.pneumoniae are implicated the gram negative bacteria that can cause pneumoniabeside urinary tract infection and nosocomial infection. Until now, to identify this bacteria there are seveval methods had been used included staining and culture, Elisa, histologic and serologic that need a long time. The goal of this research is to detect K. pneumoniae with immunocytochemistry methode using antibody of K.pneumoniae and OMP K.pneumoniae as spesific antigen. The design of this reseach was explorative descriptive. The method content of K.pneumoniae isolation, specific antigen of OMP K.pneumoniae isolation, producing antibody anti OMP K.pneumoniae, and detection this bacteria on sputum with immunocytochemistry methode respectivelly. For diagnostic test sensitivity and specificity. Analysis has been used. The result showed that molecular weight of OMP K.pneumoniae was 40 kDa, antibody of OMP K.pneumoniae couldidentify the OMP K.pneumoniae as antigen and could detect K.pneumoniae on sputum by using Western Blotting and immunocytochemistry. Sensitivity and specificity of this diagnostic testwas 90 %, 95 % consequently. Key words: Klebsiella pneumoniae, Outer Membrane Protein, Immunocytochemistry